Superovulatory protocol with equine pituitary extract (EPE) in mares crioula and the quarter horse - Farias, Deise Keli; Bunn, Silvério; De Medeiros Friso, Aimê; Neto, André Thaler; Mezzalira, Alceu; Pinto, Maicon Gaissler Lorena; De Oliveira, Rodrigo Arruda; Mozzaquatro, Fabricio Desconsi (FapUNIFESP (SciELO), 2019)
This study compared the superovulatory response of embryos donor mares of Quarter Horse (QH) and Crioula using a protocol with low dose of equine pituitary extract (EPE). Eight QH mares and six Crioula mares were monitored during 3 consecutive estrous cycles, with each cycle corresponds to a group. Control Group - monitoring of follicle growth up to the ovulation; EPE group - when the follicles reached 20 mm in diameter were administered 7 mg EPE twice daily. When the follicles achieved a diameter 35 mm, the ovulation was induced with 2500UI hCG; Post-EPE Group - idem to the control group. Data were analyzed using GLM procedure of the SAS statistical package. The variables were submitted to the Tukey’s test and least square means adjusted for multiple comparisons using the Tukey-Kramer’s test, with significance level of 5%. Values are presented as mean ± SD. In the Crioula mares treated with EPE, there was an increase in the number of ovulations (p =0.0534) with a mean of 3.33 ± 2.06 ovulations when compared to the control and post-EPE groups, and mares QM. (2.00±0.53). Treatment with EPE in the recommended dose allowed better superovulatory response and rate of embryo recovery in Crioula mares when compared to the QM mares.
SuperovulaÇÃo em Éguas da raÇa crioula e quarto de milha com extrato de pituitÁria equina (EPE)
Keywords: Embryo; Embryo transfer; Equine; Superovulation